The Effect of Farm Manure on Plant Nutrient Contents in Organic Leek Production - Mahmut TEPECİK and H. Hüsnü KAYIKÇIOĞLU and N. Tuba BARLAS and M. Kadri BOZOKALFA and Tansel KAYGISIZ AŞÇIOĞUL and Dursun EŞİYOK and Can UZMAY and Tarık AYYILMAZ (ISPEC Journal of Agricultural Sciences, 2021)
In order to meet the increase in demand for food with the increase in population, the problem of environmental pollution arises as a result of agricultural practices carried out by moving away from scientific principles. Organic agriculture, on the other hand, is an agricultural method that aims to protect and sustain the health of soil-water-and biological diversity by prioritizing food security. This study was carried out in typic xerofluvent soil to determine the effect of matured farm manure applied in different doses on yield and elemental composition of leek plant. The total N content of the macro plant nutrients of the leek in different doses of animal manure applications differed depending on the application doses. In the first year N 1.62-2.52% and in the second year 1.15-2.17%, low N values were obtained in the control application and high N values in the H3 application in both years. Phosphorus nutrient was determined as 0.41-0.60% in the first year and 0.38-0.40% in the second year. The effect of different doses of animal manure on potassium was determined as 4.72-5.79% in the first year and 4.77-5.60% in the second year, the highest K was determined as H2 (5.79%) in the first year and H3 (5.60%) in the second year, higher than other applications values were obtained. The effect of the applications on Ca content was determined as 0.42-0.52% in the first year and 0.42-0.58% in the second year. It was determined as 0.42-0.52% Mg in the first year and 0.40-0.47% in the second year. Zinc content varying between 38.85-50.04 mg kg-1 in the first year and 39.79-51.39 mg kg-1 in the second year, copper element 4.20-5.04 mg kg-1 in the first year and 2.50-3.30 mg kg-1 in the second year. The Zn content varied according to the applications, and it was determined as 29.64-39.89 mg kg-1 in the first year and 27.07-33.24 mg kg-1 in the second year. According to the aplication, manganese was determined as 16.80-23.54 mg kg-1 in the first year and 19.19-22.10 mg kg-1 in the second year.